Determinants of social entrepreneurship in Central American university students - Rojas-Segura, Javier (2025)
This study evaluates the influence of factors related to university-industry collaborations (i.e., ties to social organizations, access to internships, support by social mentors) and socially oriented business and financial education on the creation of social ventures among university students in Central America. The study applies a quantitative-qualitative design on a sample of 421 university students in five Central American countries. The quantitative analysis uses an ordered logistic regression model, whereas the qualitative study applies in-depth interviews for a sequential methodological triangulation analysis. Despite the growing importance of social entrepreneurship in Central America, there is a lack of empirical research examining the factors that influence the creation of social enterprises by university students in the Central American region with a propensity to start social enterprises. The results show that having ties to social organizations, participating in internships, receiving support from social mentors, and receiving socially oriented business and financial education positively affects the creation of social enterprises among university students in Central America.